Quantifying Quasi‐Fermi Level Splitting and Mapping its Heterogeneity in Atomically Thin Transition Metal Dichalcogenides. Issue 25 (6th May 2019) - Tebyetekerwa, Mike; Zhang, Jian; Liang, Kun; Duong, The; Neupane, Guru Prakash; Zhang, Linglong; Liu, Boqing; Truong, Thien N.; Basnet, Rabin; Qiao, Xiaojing; Yin, Zongyou; Lu, Yuerui; et al.
Abstract: One of the most fundamental parameters of any photovoltaic material is its quasi‐Fermi level splitting (∆ µ ) under illumination. This quantity represents the maximum open‐circuit voltage ( V oc ) that a solar cell fabricated from that material can achieve. Herein, a contactless, nondestructive method to quantify this parameter for atomically thin 2D transition metal dichalcogenides (TMDs) is reported. The technique is applied to quantify the upper limits of V oc that can possibly be achieved from monolayer WS2, MoS2, WSe2, and MoSe2 ‐based solar cells, and they are compared with state‐of‐the‐art perovskites. These results show that V oc values of ≈1.4, ≈1.12, ≈1.06, and ≈0.93 V can be potentially achieved from solar cells fabricated from WS2, MoS2, WSe2, and MoSe2 monolayers at 1 Sun illumination, respectively. It is also observed that ∆ µ is inhomogeneous across different regions of these monolayers. Moreover, it is attempted to engineer the observed ∆ µ heterogeneity by electrically gating the TMD monolayers in a metal‐oxide‐semiconductor structure that effectively changes the doping level of the monolayers electrostatically and improves their ∆ µ heterogeneity. The values of ∆ µ determined from this work reveal the potential of atomically thin TMDs for high‐voltage, ultralight, flexible, and eye‐transparent future solar cells. Abstract : 2D atomically thin transition metal dichalcogenides (TMDs) show a remarkable light–matter interaction and atomic thickness. The possible maximum open‐circuit voltages, one of the most important photovoltaic parameters, of monolayer TMD‐based solar cells are quantified. The values determined from this work reveal the potential of atomically thin TMDs for high‐voltage, ultralight, flexible, and eye‐transparent future photovoltaic devices.